2019
DOI: 10.1016/j.colsurfb.2019.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Probing phospholipid microbubbles by atomic force microscopy to quantify bubble mechanics and nanostructural shell properties

Abstract: Highlights  Using tapping mode imaging, the thickness of microbubble shells can be quantified  Quantifying shell thickness has significant impact on Young's Modulus values  Atomic force microscopy can be used to quantify thickness of the PEG brush layer ABSTRACT: Microbubbles (MBs), which are used as ultrasonic contrast agents, have distinct acoustic signatures which enable them to significantly enhance visualisation of the vasculature. Research is progressing to develop MBs which act as drug/gene delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…A Horizon instrument (Horizon v3, Leeds, UK) was used for all MB production with a polymethylmethacrylate (PMMA) flow-focused MF chip designed in-house and fabricated by Epigem (Redcar, UK) to prepare MBs according to methodologies previously published. , Both the liquid flow rate and gas (perfluorobutane (C 4 F 10 ) from F2 chemicals (Preston, UK)) pressure were controlled by a p-pump, a pressure-based pumping system from Dolomite (Royston, UK).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…A Horizon instrument (Horizon v3, Leeds, UK) was used for all MB production with a polymethylmethacrylate (PMMA) flow-focused MF chip designed in-house and fabricated by Epigem (Redcar, UK) to prepare MBs according to methodologies previously published. , Both the liquid flow rate and gas (perfluorobutane (C 4 F 10 ) from F2 chemicals (Preston, UK)) pressure were controlled by a p-pump, a pressure-based pumping system from Dolomite (Royston, UK).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Physically, √ ε is the ratio of the typical time scale τ 0 = d e ρ s /E needed for an elastic wave to travel across the shell thickness d e over the time scale ω −1 0 of the motion of the boundary. In general, E is not smaller than 100 MPa for a polymeric material where d e ∼ 100 nm, but for lipid shells of thickness of order 5 nm which are made of the type of anisotropic material that we treat later on in this paper, orders of magnitude as low as 100 kPa were proposed for an effective isotropic Young modulus (Shafi et al, 2019).…”
Section: Modelmentioning
confidence: 96%
“…The atomic force microscopy (AFM) is a direct approach used to estimate UCAs' properties. However, depending on the model used to extract elastic constants from the force-displacement curve of an AFM, very different values can be found (Abou-Saleh et al, 2013;Buchner Santos et al, 2012;Lytra et al, 2020;Shafi et al, 2019). This makes the validation of spherical oscillation models a tricky task so far.…”
Section: Confrontation With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though EBs are widely used for ultrasound medical imaging, in particular, a recent study Errico et al (2015) have shown that these bubbles can not only be used as rough contrast agents, rather can also be used as traces to extract vascular geometry (microvascular imaging) and blood flow velocity over a large dynamic range in microns length scales. The encapsulation of such bubbles can be made up of polymers (Liu et al 2014;Song et al 2018), proteins (Wang et al 2020) or phospholipids (Santos et al 2012;Li et al 2013a;Abou-Saleh et al 2013;Gong et al 2014;Parrales et al 2014;van Rooij et al 2015;Segers et al 2016;Lum et al 2016;Helfield 2019;Shafi et al 2019;Segers et al 2020). Thus experimental and theoretical understanding of the response of EBs to the external acoustic field is of great importance for the future developments of these promising applications/techniques.…”
Section: Introductionmentioning
confidence: 99%